Comparison in quality of life and pain between fixed and mobile bearing implants in total knee arthroplasty - mustafa, hussain; Nadeem, Zohaib; Hafeez, Sohail; Sami, Arsal; Afreen, Mahrukh (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the outcomes of fixed versus mobile platform total knee arthroplasty in terms of postoperative pain, function and quality of life. Method: The retrospective, comparative study was conducted at the Shifa International Hospital, Islamabad, Pakistan, and comprised data from January 2023 to June 2024 of patients requiring total knee arthroplasty. Based on the prosthesis type implanted, the patients were divided into fixed-platform Group A, and mobile-platform Group B. The patients were assessed at 6 months and 1 year post-intervention for pain, function and quality of life using visual analogue scale, Western Ontario and McMaster University Arthritis Index and Short Form Health Survey, respectively. Data was analysed using SPSS 22. Results: Of the 62 patients, 31(50%) were in Group A; 23(74.19%) female and 8(25.81%) male with mean age 62.68±5.46 years. The remaining 31(50%) patients were in Group B; 20(65.52%) female and 11(35.48%) male with mean age 68.87±5.72 years. Mean scores on all the parameters were significantly different between the groups at 12-month follow-up (p<0.05). Conclusion: Mobile-platform total knee arthroplasty provided much better outcomes at short-term follow-up compared to fixed-platform total knee arthroplasty. Key Words: Arthroplasty, Knee joint, Quality of life, Visual analogue scale.